1997
DOI: 10.1002/1521-3951(199706)201:2<361::aid-pssb361>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on the Structure and Lattice Dynamics of Fullerene Crystal C60

Abstract: The low‐temperature orientationally ordered crystalline phase of fullerene C60 was investigated in dependence on the external pressure. An assumption was made that the energy of the lattice includes two contributions: a Lennard‐Jones (12–6) potential and electrostatic interaction. The vibrational spectrum of C60 crystal was calculated using the atom–atom potential method. The frequencies of intermolecular modes as functions of external pressure were studied. The sound velocities, elastic constants and bulk mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The limiting intermolecular spectrum of hydrated microcrystal C 60 is represented in table 2. As we can see the calculated vibrational frequencies lie lower the fundamental modes for solid C 60 [18].…”
Section: Study Of Vibrational Spectrum Of Fullerene Aggregates C 60 Isupporting
confidence: 65%
See 2 more Smart Citations
“…The limiting intermolecular spectrum of hydrated microcrystal C 60 is represented in table 2. As we can see the calculated vibrational frequencies lie lower the fundamental modes for solid C 60 [18].…”
Section: Study Of Vibrational Spectrum Of Fullerene Aggregates C 60 Isupporting
confidence: 65%
“…The numerical calculations were carried out in the approximation of a Lennard-Jones (12−6) atom-atom potential only (the entropy factor did not consider because an assumption was made that the formation of orientationally ordered structures in water takes place [12]) using the proposed molecular dynamics model for a fullerene crystal C 60 [18].…”
Section: Study Of Vibrational Spectrum Of Fullerene Aggregates C 60 Imentioning
confidence: 62%
See 1 more Smart Citation
“…In particular, such molecules as benzene, xylene, toluene, CCl 4 et al easily penetrate into the interplanar gaps, forming tight solvate complexes, the destruction of which occurs only when fullerite is heated up to 400–500 K . It has been found that at high temperatures and pressures fullerite solvated by organic substances can be transformed into compound, having higher hardness than diamond .…”
Section: Introductionmentioning
confidence: 99%